KATP channels modulate intrinsic firing activity of immature entorhinal cortex layer III neurons - Lemak, Maria S.; Voloshanenko, Oksana; Draguhn, Andreas; Egorov, Alexei V. (Frontiers in Cellular Neuroscience, 2014)
Medial temporal lobe structures are essential for memory formation which is associated with coherent network oscillations. During ontogenesis, these highly organized patterns develop from distinct, less synchronized forms of network activity. This maturation process goes along with marked changes in intrinsic firing patterns of individual neurons. One critical factor determining neuronal excitability is activity of ATP-sensitive K+ channels (KATP channels) which coupled electrical activity to metabolic state. Here, we examined the role of KATP channels for intrinsic firing patterns and emerging network activity in the immature medial entorhinal cortex (mEC) of rats. Western blot analysis of Kir6.2 (a subunit of the KATP channel) confirmed expression of this protein in the immature entorhinal cortex. Neuronal activity was monitored by field potential (fp) and whole-cell recordings from layer III of the mEC in horizontal brain slices obtained at postnatal day (P) 6-13. Spontaneous fp-bursts were suppressed by the KATP channel opener diazoxide and prolonged after blockade of KATP channels by glibenclamide. Immature mEC LIII principal neurons displayed two dominant intrinsic firing patterns, prolonged bursts or regular firing activity, respectively. Burst discharges were suppressed by the KATP channel openers diazoxide and NN414, and enhanced by the KATP channel blockers tolbutamide and glibenclamide. Activity of regularly firing neurons was modulated in a frequency-dependent manner: the diazoxide-mediated reduction of firing correlated negatively with basal frequency, while the tolbutamide-mediated increase of firing showed a positive correlation. These data are in line with an activity-dependent regulation of KATP channel activity. Together, KATP channels exert powerful modulation of intrinsic firing patterns and network activity in the immature mEC.